Intestinal flora: A new target for traditional Chinese medicine to improve lipid metabolism disorders - Liu, Min; Shi, Wei; Huang, Yefang; Wu, Yeke; Wu, Keming (Frontiers in Pharmacology, 2023)
Lipid metabolism disorders (LMD) can cause a series of metabolic diseases, including hyperlipidemia, obesity, non-alcoholic fatty liver disease (NAFLD) and atherosclerosis (AS). Its development is caused by more pathogenic factors, among which intestinal flora dysbiosis is considered to be an important pathogenic mechanism of LMD. In recent years, the research on intestinal flora has made great progress, opening up new perspectives on the occurrence and therapeutic effects of diseases. With its complex composition and wide range of targets, traditional Chinese medicine (TCM) is widely used to prevent and treat LMD. This review takes intestinal flora as a target, elaborates on the scientific connotation of TCM in the treatment of LMD, updates the therapeutic thinking of LMD, and provides a reference for clinical diagnosis and treatment.